The Use of Game Based Learning on Student’s Speaking Skill and Speaking Anxiety: An Experimental Research at Seventh Grade of MTs YASMU - Chichik Mursyidah (JEET, Journal of English Education and Technology, 2022)
Speaking is one of important skill that we have mastered in English. Its make us easier to get a new friend. Besides, speaking is a difficult skill to be mastered by learners because speaking combines the parts of writing and listening. This research goals at investigating the use of game based learning on students’ speaking skill and students’ speaking anxiety. The researcher used a quantitative method with a pre-experimental design by using the validity and reliability test instrument. The population in this research was seventh class grade MTs YASMU Manyarejo Manyar Gresik. Collecting data using a test, one class was given a pre-test before treatment and a post-test after treatment. Then data analysis using SPSS or Manual counting with the formula paired simple t-test. The result showed that the experimental group scores had a significant difference before being taught the game based learning method. It can be said with more than 95% confidence, that the anxiety mean in control and experimental group before using game based learning was not significantly different. Therefore, the results revealed that balancing as a stress-free tool of learning has the potentially of reducing students’ anxiety to improve their speaking skill.